Macroeconomic variables and corruption in Malaysia / Zahariah Mohd Zain …[et al.] - Mohd Zain, Zahariah; Setapa, Fatimah; Baah, Ruzita; Kusnin, Khaleed (Universiti Teknologi MARA Cawangan Selangor, 2019)
Despite the government’s effort to eradicate corruption, it is still impossible to combat it as long as individuals with no integrity and sense of responsibility exists in organizations. ca This study is to investigate the relationship between several macroeconomics variables with corruption. The macroeconomics variables include government spending, human capital, investment and trade openness. This study uses time series data from the year 1994-2016. The data were obtained from Political Risk Service (PRS) and World Development Indicator from World Bank. Ordinary Least Square (OLS) method is used to examine the relationship between all the macroeconomic variables and corruption. The macroeconomic variables found to be significantly related to corruption in Malaysia were human capital and trade openness. However changes in the corruption in Malaysia may not necessarily be influenced by government spending and investment. Furthermore, all variables are found to have a positive relationship with corruption. The general findings of this paper strongly suggested that corruption in Malaysia is increasing continuously. Therefore efforts by the Malaysian government and policy makers are badly needed to fight corruption in order to foster better economic growth through improved business operations, employment and investments.